A repercussão midiática das mensagens na camisa do corinthians nos sites esportivos Lance Net, Globo Esporte e ESPN - Arroyo, Gabriel [UNESP] (2014)
This dissertation analyzes the communicative possibilities of football shhirt as part of the sports media process. In the years 2011, 2012 and 2013, the football team Sport Club Corinthians Paulista, used constantly in thsi shirt messagining game with different themes, from social problems, natural disasters, logos and various NGOs among other honors. The use of the shirt as communication performed by the team transcends the barrier of aesthetic and visual, using his shirt as a carrier and distributor of information within and off the pitch, when the message is legitimized with the impact of the media, especially in sites sports: Globe sports, ESPN and Lance Net. Cultural studies of the third generation, the authours focus on the research of the intentions of the media, helped to elucidate the process of building media about media phenomenon, since the creation of the message by the marketing department of the team until the acceptance and continuation of materials in sports websites. To investigate the interests of the team in producing the messages and media pass on the phenomenon, it was necessary to collect the releases posted on the official website of the team an build bulletin analyzes the posts passed on 3 sites observed, were used for both studies newsmaking Mauro Wolf and the concepts of newsworthiness Nelson Teasing. The survey also included the technique of observation and collection, using the method of content analysis allowed to quantify and categorize the actions that allowed later perform the triangluation of data to understand the intentions of the Corinthians in the production of messages and the alleged reasons for media reflect them